Development of Slurry Surfacing with Electric Arc Furnace Slag for Pavements with Friction Problems - Terrones Saeta, Juan María; Suárez Macías, Jorge; Iglesias, Francisco Javier; Corpas Iglesias, Francisco Antonio (MDPI, 2024)
Pavement maintenance is an essential activity for maintaining the quality of the pavements. It is common for the ageing pavement to present problems of friction, so a proper solution must be provided. In this work, electric arc furnace slags are incorporated in slurry surfacing to provide adequate friction with this technique. The electric arc furnace slag was studied with physical, chemical, and mechanical tests to evaluate its suitability in the formation of the bituminous mixture. At the same time, different groups of samples were made with increasing percentages of bitumen emulsion and slag as coarse aggregate, determining the wear of the different families and the cohesion. The results reflected the excellent characteristics of the electric arc furnace slags, and an optimal combination of materials (slag, aggregate, water, and bitumen emulsion) could be obtained to develop slurry surfacing applicable to important traffic roads. This provided a use for the electric arc furnace slag in which its mechanical properties were used and a sustainable bituminous mixture with excellent characteristics and respectful of the environment was developed.
Keywords: slurry surfacing; electric arc furnace slag; bitumen emulsion; friction; sustainability; pavement